PENGARUH E-SERVICE QUALITY TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION PADA TOKO ON LINE BUKA LAPAK - Ahmad Irwansyah; Riko Mappadeceng (Universitas Batanghari, 2018)
Along with the development of an increasingly modern era, information technology is growing very rapidly. This is because all information required can be obtained easily and quickly via the internet. The development of the internet today not only serves as a medium of information, but the internet can also be utilized for the benefit of the business as a business online using a service-based website. The website-based services in many of the important components in it to achieve success in business, one of which is the quality of service (E-Service Quality). The company provides e-service quality the higher the customer then it will give rise to customer satisfaction, and in a long period of time will certainly generate customer loyalty. E-service quality is defined as the assessment and evaluation of the quality of the overall service delivery to consumers in a virtual market. Word of satisfaction or satisfaction derived from the Latin